2013
DOI: 10.1016/j.jcct.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outcomes with coronary artery calcium scanning in unselected populations: The Multi-Ethnic Study of Atherosclerosis (MESA) and Heinz Nixdorf RECALL study (HNR)

Abstract: Background The Multi-Ethnic Study of Atherosclerosis (MESA) and the Heinz Nixdorf Recall Study (HNR)) differed in regards to informing physicians and patients of the results of their subclinical atherosclerosis. Objective This study investigates whether the association of coronary artery calcium (CAC) with incident non-fatal and fatal cardiovascular (CVD) events is different among these two large, population-based observational studies. Methods All Caucasian subjects aged 45–75 years, free of baseline card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
4
28
0
1
Order By: Relevance
“…Its relation to coronary artery atherosclerosis have been confirmed by histopathologic studies [16] and it has been shown to be strong predictor of incident coronary heart disease and improve predictive information compared to standard risk factors in large multi ethnic cohort studies. [17,18].…”
Section: Prevalence Of Coronary Artery Calcium In Diabetic Patientsmentioning
confidence: 99%
“…Its relation to coronary artery atherosclerosis have been confirmed by histopathologic studies [16] and it has been shown to be strong predictor of incident coronary heart disease and improve predictive information compared to standard risk factors in large multi ethnic cohort studies. [17,18].…”
Section: Prevalence Of Coronary Artery Calcium In Diabetic Patientsmentioning
confidence: 99%
“…3 By contrast, 9.8% (ie, ≈10%) of subjects revealed CAC scores ≥400, which is commonly considered as cut off for the highest CAC category. 1,14,15 To further evaluate effects of atherosclerosis markers on stroke risk, we calculated crude stroke incidence rates for categories below and above the 90th CIMT percentile and categories above and below the 10th ABI percentile, equivalent to the CAC ≥400 cut off (Figure 1). These analyses revealed that both CIMT and ABI provided additional information about stroke risk when combined with CAC ( Figure 1A and 1B), as did CIMT combined with ABI ( Figure 1C).…”
Section: Stroke Risk In Different Cac Cimt and Abi Categoriesmentioning
confidence: 99%
“…In the HNR cohort, 9.8% and 27.2% of subjects revealed CAC scores ≥400 and ≥100, respectively, which are widely used as cut offs for the highest and second-highest CAC category. 1,14,15 ABI differs from CAC and CIMT with respect to that low ABI values are rare in the general population, representing a hallmark of advanced atherosclerosis. Thus, only 4.8% of subjects in the 3 Although reflecting a simple risk predictor that does not require expensive technical equipment, its practical use is limited by the fact that >20 subjects in the general population need to be screened in order that a single subject with reduced ABI is detected.…”
Section: In Chs [Pittsburgh])mentioning
confidence: 99%
“…High event rates similar to rates in secondary prevention populations have been noted for CAC scores >100 (29,32), and that alternate threshold may also be considered for determining eligibility for statin therapy. Furthermore, a CAC >75th percentile score does not confer the same very high risk status as a score >300 or >100, although these are viewed as equivalent options in the RAG.…”
Section: Subclinical Atherosclerosis Assessmentmentioning
confidence: 86%